A Lightweight Aggregation Scheme for Multidimensional Charging Privacy Data based on Consortium Blockchain - Wang, Guilan; Cui, Jian; Duo, Chunhong (International Journal of Electric Power and Energy Studies, 2026)
With the growing integration of charging piles into the smart grid, efficiently aggregating privacy-containing charging data, dynamically optimizing charging strategies, and enhancing charging efficiency have become key future development directions. Current data aggregation schemes, mostly based on homomorphic encryption, place high computational demands on charging piles and may lead to centralized data management issues. To address these challenges, a lightweight data aggregation scheme based on consortium blockchain is proposed. Firstly, non-interactive symmetric encryption and aggregate signatures are used to reduce computational and communication overhead. Symmetric encryption ensures efficient encryption and decryption processes, while aggregate signatures compress multiple signatures into one, reducing storage and verification costs. Secondly, a hierarchical distributed data aggregation model is designed to achieve decentralization, distributing aggregation tasks across multiple layers to enhance system scalability and robustness. Thirdly, a dual-layer consensus algorithm is proposed based on the architecture of charging piles and edge cloud servers. This algorithm ensures low latency and system robustness at the charging pile layer, while the edge cloud server layer can resist Byzantine attacks. By balancing efficiency and security, this approach optimizes resource utilization and enhances privacy protection. Finally, experiments demonstrate that the proposed scheme significantly reduces computational and communication overhead and improves efficiency.